(untitled) (Nonconventional Technologies Review, 2016)
The paper presents the design and implementation of an automatic tool measurement system using a infrared reflective optical sensor.The system in used on the TMA 5 axis machining centre for tool measuring purposes, having the capability of autonomous operation, the measuring process is done automatically by the CNC equipment.